Concrete Stiffened Steel Plate Shear Walls With an Unstiffened Opening. (November 2017) - Shafaei, Soheil; Farahbod, Farhang; Ayazi, Amir
Abstract: In this study, nonlinear behavior of concrete stiffened steel plate shear wall (CSPSW) with an opening is investigated. The study is divided into two separate parts in order to understand the effect of an unstiffened opening—locations and sizes. In phase one: four square opening sizes—small, medium, large, and very large—are selected to study the location of the opening. When the size of square opening is fixed, the location is changed over the infill wall. The pattern is also repeated with a new square size. In phase two: shear walls with a centrally located circular opening are considered and the opening ratio varies from 10% to 65%. In the study, the degradations of seismic factors —the initial stiffness, the ultimate shear strength, the ductility ratio, and the energy absorption— in terms of opening ratio are calculated. According to obtained results, the behavior of CSPSWs with an opening is utterly different from corresponding SPSWs. Initial elastic stiffness of CSPSWs with an opening is independent of the opening location and ultimate shear strength is slightly affected by location. Moreover, a linear degradation in the initial elastic stiffness and the ultimate shear strength of the infill composite wall is observed due to increasing the opening ratio.